PERAN BADAN PENGAWAS OBAT DAN MAKANAN DALAM PENGAWASAN PEREDARAN OBAT BERLOGO BIRU DI LUAR SARANA FARMASI DI KOTA PEKANBARU - Refika Wahyuni; Gusliana HB; Muhammad A. Rauf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Based on Law Number 36 of 2009 concerning Health Article 98paragraph (2), it is explained that drug distribution can be circulated by partieswho have authority in their fields. Furthermore, it is explained in the PresidentialRegulation Number 80 of 2017 concerning the Drug and Food Control AgencyArticle letters (b) and (c), that the Drug and Food Control Agency has theauthority to carry out intelligence and investigations in the field of drug control inaccordance with statutory regulations and imposing sanctions administrative inaccordance with the provisions of the legislation. So with that, minimarkets orgrocery toll roads are not allowed to sell or distribute drugs without a drugstorepermit.In this study using empirical legal research methods, which collected datausing interviews, questionnaires, library research and observation of researchersin the city of Pekanbaru. While the population and sample in this study are theHead of the Center for Drug and Food Control in Pekanbaru, the Head of thePekanbaru City Health Service, Indomaret, Alfamart and grocery stores in thePekanbaru city areaFrom the results of research conducted by researchers, it can beconcluded that there are three main elements, namely, first, that the Food andDrug Supervisory Agency has not carried out optimal supervision. Second, theinhibiting factors for the Drug and Food Control Agency in carrying out its roleare the large number of existing facilities at Pekanbaru, the lack of humanresources at the Drug and Food Control Agency in Pekanbaru, the lack of publicknowledge of the applicable laws regarding drug distribution, not adherence ofbusiness actors to the applicable book rules regarding the distribution of drugsoutside pharmaceutical facilities in Pekanbaru City. Kenga Efforts that have beenmade by the Food and Drug Supervisory Agency, namely by providing educationto the public or business actors providing supervisors on the spot if irregularitiesare found at the place, giving administrative sanctions such as a warning to thetemporary closing of the place of business.Keywords: BPOM – Control - Drug Distribution